Clinical and Laboratory Features of PCR-Confirmed and Clinically Suspected COVID-19 Pediatric Patients: A Single Hospital-Based Experience During the First COVID-19 Wave in the United Arab Emirates - Eldin, Nashwa M. B.; Saleh, Maysa; Labib, Bahaaeldin; Othman, Marwa; Chacko, Lalu; Mae, Daphne; Elnour, Lamiaa; Al-Rifai, Rami H. (Frontiers in Pediatrics, 2022)
Objective: This study investigated clinical and laboratory differences between confirmed (RT-PCR-positive) and clinically-suspected (RT-PCR-negative) COVID-19 pediatric patients, and explored factors associated with disease severity at presentation and duration of hospitalization. Methods: Medical charts of COVID-19-confirmed and clinically-suspected pediatrics admitted to a tertiary hospital in Abu Dhabi Emirate were reviewed. Sociodemographics, clinical, laboratory, and clinical outcomes were retrieved and analyzed. Results: Between April 1 to June 30, 2020, 173 patients (mean age: 3.6 ± SD 3.2 years) presented with respiratory symptoms. Of them, 18.0% contacted confirmed COVID-19 cases, 66.5% had symptoms since ≤3 days, and 86.7% were with moderate to severe disease. Twenty-eight (16.1%) patients tested positive while the rest (83.8%) tested negative in RT-PCR. COVID-19-confirmed and clinically-suspected patients were statistically similar (p>0.05) in all sociodemographics, disease severity, and vital signs except residence status (89.3% vs 58.6% were residents, respectively, p=0.002) and contacting confirmed COVID-19 cases (82.1% vs 5.5%, respectively, p<0.001). Fever (100% and 91.0%) and cough (100% and 95.9%) were most common symptoms in both confirmed and clinically suspected COVID-19 patients. All patients were statistically comparable in mean white blood cells and platelets count, and hemoglobin concentration, except in mean concentration of neutrophils (higher in clinically-suspected, p = 0.019). C-reactive protein was 2-time higher in clinically-suspected compared to confirmed patients (p = 0.043). Lymphocyte (OR: 1.31, p<0.001), LDH (OR: 1.01, p=0.001), D-Dimer (OR: 1.92, p<0.001), ferritin level after 24-36 hours (OR: 9.25, p<0.05), and SGPT (OR: 1.04, p<0.05) were all associated with disease severity. Elevated ferritin (>300 µg/L) after 24-36 hours was the only correlated factor with disease severity (aOR: 17.38, p<0.05). Confirmed compared with clinically-suspected (aOR: 4.00, 95% CI: 2.92–5.10) and pediatrics with moderate compared with mild disease (aOR: 5.87, 95% CI: 1.08–32.06) had longer hospitalization. Conclusion In pediatric patients with negative RT-PCR, COVID-19 is still suspected based on clinical symptoms and epidemiological data. A tentative diagnosis can be made based on a thorough examination and proper medical management can be initiated promptly.